Separation and partitioning of Green Fluorescent Protein from Escherichia coli homogenate in poly(ethylene glycol)/sodium-poly(acrylate) aqueous two-phase systems - Johansson, Hans-Olof; Ishii, Marina; Minaguti, Mariane; Feitosa, Eloi [UNESP]; Vessoni Penna, Thereza Christina; Pessoa, Adalberto (Elsevier B.V., 2008)
The partitioning of Green Fluorescent Protein (GFP) in poly(ethylene glycol)/Na-poly(acrylate) aqueous two-phase systems (PEG/NaPA-ATPS) has been investigated. The aqueous two-phase systems are formed by mixing the polymers with a salt and a protein solution. The protein partitioning in the two-phase system was investigated at 25 degrees C. The concentration of the GFP was measured by fluorimetry. It was found that the partitioning of GFP depends on the salt type, pH and concentration of PEG. The data indicates that GFP partitions more strongly to the PEG phase in presence of Na2SO4 relative to NaCl. Furthermore, the GFP partitions more to the PEG phase at higher pH. The partition to the PEG phase is strongly favoured in systems with larger tie-line lengths (i.e. systems with higher polymer concentrations). The molecular weight of PEG is important since the partition coefficient (K) of GFP gradually decreases with increasing PEG size, from K ca. 300-400 for PEG 400 to K equal to 1.19 for PEG 8000. A separation process was developed where GFP was separated from a homogenate in two extraction steps: the GFP is first partitioned to the PEG phase in a PEG 3000/NaPA 8000 system containing 3 wt% Na2SO4, where the K value of GFP was 8. The GFP is then re-extracted to a salt phase formed by mixing the previous top-phase with a Na2SO4 solution. The K-value of GFP in this back-extraction was 0.22. The total recovery based on the start material was 74%. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: two-phase; Partitioning; poly(acrylic acid); Polyethylene glycol; Protein